Charge Transfer from Methylammonium Lead Iodide Perovskite to Organic Transport Materials: Efficiencies, Transfer Rates, and Interfacial Recombination. Issue 13 (17th February 2017) - Hutter, Eline M.; Hofman, Jan‐Jaap; Petrus, Michiel L.; Moes, Michiel; Abellón, Ruben D.; Docampo, Pablo; Savenije, Tom J.
Abstract : Perovskite‐based photovoltaics have been rapidly developed, with record power conversion efficiencies now exceeding 22%. In order to rationally design efficient and stable perovskite solar cells, it is important to understand not only charge trapping and recombination events, but also processes occurring at the perovskite/transport material (TM) interface, such as charge transfer and interfacial recombination. In this work, time‐resolved microwave conductivity measurements are performed to investigate these interfacial processes for methylammonium lead iodide and various state‐of‐the‐art organic TMs. A global kinetic model is developed, which accurately describes both the dynamics of excess charges in the perovskite layer and transfer to charge‐specific TMs. The authors conclude that for state‐of‐the‐art materials, such as Spiro‐OMeTAD and PCBM, the charge extraction efficiency is not significantly affected by intra‐band gap traps for trap densities under 10 15 cm –3 . Finally, the transfer rates to C60, PCBM, EDOT‐OMeTPA, and Spiro‐OMeTAD are sufficient to outcompete second order recombination under excitation densities representative for illumination by AM1.5. Abstract : The dynamics of charge transfer from CH3 NH3 PbI3 to charge‐specific transport materials are revealed using time‐resolved microwave conductivity measurements and a global kinetic model. Hence, the authors find that the transfer rates to C60, PCBM, EDOT‐OMeTPA, and Spiro‐OMeTAD are sufficient to outcompete other recombination pathways at excitation densities representative for AM1.5, while this is not the case for bis‐PCBM, ICBA, and H101.